Reviewer - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Paper Writting Stipulation Papers on JIFAM - The Journal of Infrastructure & Facility Asset Management Journal is regulated by general stipulation as follows. - Papers must be a real work of the author. - Papers has never been published in other media. - Papers must contain discussion about Infrastructure & Facility Asset Management. - Papers must contains a new discussion, judging based on the discussion that has been published in previous JIFAM. - The paper has to take references from Scientific Journal with minimum of 5 papers. - Paper lengths are limited in 8-16 pages. - Paper Template can be downloaded on the website http://https://iptek.its.ac.id/index.php/jifam Scope of Topic JIFAM accepts papers on Infrastructure & Facility Asset Management. The scope of the topic includes, but not limited, of the following. - I & F Function - I & F Demand - Supply - I & F User Behavior - I & F Policy - I & F Planning - I & F Administration Aspects - I & F Operation System - I & F Maintenance System - I & F Evaluation Technique - I & F Disposal - I & F Economical Aspect - I & F Financial Aspect - I & F Management Organization - I & F Spatial Aspects and Environmental Aspects · Mahendra A. Maulana, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia · Januarti Jaya Ekaputri, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia · Trihanyndio Rendi Satrya, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia · Djoko Legono, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia · Anastasia Caroline Sutandi, Universitas Parahyangan, Bandung · Hitapriya Suprayitno, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia · Eko Budi Santoso, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia · Satria Darmanegara, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia · Mahendra A. Maulana, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia · Januarti Jaya Ekaputri, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia · Trihanyndio Rendi Satrya, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia · Djoko Legono, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia · Anastasia Caroline Sutandi, Universitas Parahyangan, Bandung · Hitapriya Suprayitno, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia · Eko Budi Santoso, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia · Satria Darmanegara, Institut Teknologi Sepuluh Nopember (ITS), Surabaya, Indonesia